A method for along-wind vibration control of chimneys by tuning liners. (1st February 2022) - Cheng, Yusong; Dai, Kaoshan; Liu, Yangzhao; Yang, Han; Sun, Mengran; Huang, Zhenhua; Camara, Alfredo; Yin, Yexian
Highlights: A method to reduce the vibration of chimneys by tuning the suspended liners is proposed. A simplified model of chimney with liners for the numerical analysis is introduced. Conceptual design and optimization methods are proposed for the tuned structure. Abstract: Reinforced concrete chimneys with steel liners are widely used in waste gas discharge of industrial facilities, and guaranteeing their safety performance in harsh environments is important for industries and society. This paper proposes a novel method for the reduction of along-wind vibration in chimneys with liners by tuning the movement of the suspended liners to the response of the outer cylinder, and the conventional rigid supporting platform is replaced by a combination of radial horizontal tuning systems and vertical suspension systems. This 'tuned liners' method is applied to a simplified beam-like model that is able to capture the liners/chimney interaction and is validated against a more detailed finite-element shell model. A design method is proposed to obtain parameters of the tuning system that lead to significant reductions of along-wind vibrations whilst satisfying the relative response requirement. A comprehensive study of the structural vibration under stochastic wind actions is performed to demonstrate the effectiveness of the proposed system. The characteristics of the relative vibration of the outer cylinder and the liners are studied. Comparison with conventional TMD solution is conducted to further explore the advantage of the tuned-liners system under stochastic wind actions. The results indicate that the top displacement and acceleration of the outer cylinder are effectively reduced by 62% and 70% with the tuned liners, respectively. A similar performance using a conventional TMD would require an auxiliary vibrating mass that is approximately 300 tons, which is avoided with the proposed tuned liners. Results show that the proposed technique could be effective in the along-wind control of chimneys in multiple directions, even with some unintentional eccentricities.